ON DEVELOPING MATERIALS FOR CLIL - Cimermanová, Ivana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Content and language integrated learning (CLIL) is not an unknown term. In Slovakia, many schools communicate they apply CLIL methodology; however, there are numerous studies that are sceptical about CLIL application. The most significant problem defined by CLIL teachers is the lack of appropriate materials that follow dual aims. Based on this feedback the development of CLIL materials became a part of pre-service teachers’ methodology courses. The present study aimed to explore the attitudes of the pre-service teachers towards the possible application of the content and language integrated learning in their teaching. Questionnaires and pre-service teachers’ portfolios provided data from 63 participants. The study also presents the results of discussions on the problems faced by students, the attitudes of student teachers towards material evaluation and development, planning CLIL lessons and the analysis of the questionnaire focussing on students’ attitudes towards CLIL application. Data suggest that even though pre-service teachers are positive about CLIL application and are interested in doing CLIL lessons they do not feel confident especially in evaluating the outcomes of CLIL lessons and creating materials for CLIL lessons. Finally, the author summarises the pedagogical implications to pre-service teachers study programmes as well as recommendations for teaching practice.